2016
DOI: 10.1002/adem.201600633
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Effects on the Toughness of a High Co–Ni Steel

Abstract: Purpose of this work is to investigate the effects of reverted and retained austenite on the fracture toughness of high Co-Ni steels. Different cryogenic and tempering treatments are applied to a high Co-Ni steel in order to alter the austenite content, its chemical composition and hence its stability against transformation to martensite. Austenite stability is analyzed by applying thermal cycles in the dilatometerand by X-ray diffraction. For each heat treatment, the fracture toughness is characterized by J-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…However, the fracture toughness of materials illustrates the resistance ability (energy absorption) to stable crack propagation, as revealed by the R curve in Figure c. The R curve represents the energy for the formation of plastic deformation zone ahead of the crack tip, initiation and growth‐coalescence of micro‐cracks.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fracture toughness of materials illustrates the resistance ability (energy absorption) to stable crack propagation, as revealed by the R curve in Figure c. The R curve represents the energy for the formation of plastic deformation zone ahead of the crack tip, initiation and growth‐coalescence of micro‐cracks.…”
Section: Discussionmentioning
confidence: 99%
“…The peak strength of the secondary hardening for AerMet 100 steel could be obtained by tempering around 482 • C, which gives rise to the full precipitation of M 2 C carbides [10,11]. The M 2 C carbides in high Co-Ni secondary hardening steels are needle-shaped and coherent with a martensitic matrix at the stage of peak secondary hardening [10][11][12][13][14], and it has been proven that the M 2 C carbides have a hexagonal structure [15][16][17][18][19][20]. Recent research results indicate that [7] M 2 C carbides with a hexagonal structure firstly nucleated and then grew slowly in the case of AerMet 100 steel during tempering at 482 • C, and this process was dominated by needle-shaped precipitates when tempering for 7 h or less.…”
Section: Introductionmentioning
confidence: 99%
“…The toughening behavior of high Co-Ni secondary hardening steels was due to the reversed austenite at the lath and block boundaries of martensite, as well as a decrease in the dislocation density during the tempering progress, owing to the fact that the austenite layer could prompt the advancing crack to divert, branch, and become blunt [17]. Previous research, using simulation, has indicated that the thickness of the austenite layer had a significant effect on the fracture toughness of the steels with martensite as matrix, but the angles between the austenite layer and the initial crack propagation direction had little effect on K IC [18]. At present, one explanation for the mechanism of austenite reverse transformation during the tempering process of high Co-Ni ultra-high strength steel is that [19] the formation of reverted austenite during tempering is dependent on a redistribution of substitutional atoms such as Ni, Co, and Cr; that is, the occurrence of the austenite's reverse behavior is based on the significant difference in the diffusion and migration rates of these atoms in martensite and the retained austenite during the tempering process.…”
Section: Introductionmentioning
confidence: 99%